La animación teatral: los procesos de evaluación de intervenciones socioculturales implementadas por medio de técnicas y elementos teatrales - úcar, Xavier (Teoría de la Educación. Revista Interuniversitaria, 2009)
One of the most complex processes in the socio cultural interventions is the evaluation. In this article is presented the theorical development wich leads to the design and elaboration of a multiinstrumental tool that enables the evaluation of the multicultural animation (multicultural development) processes implemented through theatre. In the same way the results obtained after its application to eight initiatives of this characteristics are presented.